Efektivitas Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Desain Grafis Siswa pada Mata Pelajaran Proses Cetak Digital pada Kelas XI Jurusan Grafika (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to evaluate the effectiveness of problem-based learning (PBL) in improving the graphic design skills of 11th grade students majoring in graphics in the subject of Digital Printing Process using CorelDraw. The background of this study stems from the low creativity and design skills of students due to conventional learning methods that are still teacher-centered. The method used is a quasi-experiment with a non-equivalent pretest-posttest control group design. Data were collected through observation, tests (pretest and posttest), and questionnaires. The data were then analyzed descriptively and quantitatively. The results indicate that the implementation of PBL significantly enhances students’ learning motivation, higher-order thinking skills (HOTS), and graphic design learning outcomes. The Mann-Whitney test produced a significance value of 0.000 < 0.05, confirming a significant difference in effectiveness between the experimental and control classes. The average N-Gain value was 0.8293, categorized as high (g > 0.7). The validity test showed that the research instruments were valid (r_calculated > r_table = 0.805), and the reliability test with Cronbach’s Alpha > 0.6 indicated that the instruments were reliable. The average pretest score of 62.42 increased to 93.94 after implementing PBL. Therefore, it can be concluded that the Problem-Based Learning model is effective in improving students’ graphic design abilities in the Digital Printing Process subject.